A232 AUTONOMIC FUNCTION ANALYSIS VIA HEART RATE VARIABILITY ASSOCIATED WITH PROPULSIVE MOTOR PATTERNS OF THE HUMAN COLON. (4th March 2021) - Ali, M; Liu, L; Chen, J; Huizinga, J D
Abstract: Background: Although parasympathetic activity is the primary driver of colonic propulsive activity, and sympathetic activity a major inhibitor of colonic motility, they are rarely measured and almost play no role in diagnosis of dysfunction or standard treatments. Aims: Our aim was to develop assessment of autonomic nervous system activity associated with the major propulsive motor patterns, an essential part of defecation reflexes in the human colon orchestrated by neural reflexes. Methods: One hundred and forty-five motor patterns were recorded from eleven healthy volunteers using high resolution colonic manometry (HRCM) with concurrent electro- and impedance cardiography to evaluate changes in parameters of heart rate variability (HRV). Results: High-amplitude propagating pressure waves (HAPWs) that often start in the proximal colon, traverse distally and end with anal sphincter relaxation, were associated with a 8.2% (P<0.02) increase in the respiratory sinus arrhythmia (RSA) value, a 24.6% increase in the root mean square of successive differences of beat to beat intervals (RMSSD), indicated a strong parasympathetic reactivity that subsided within 2 min of termination of the HAPW (Figure 1). The measure of sympathetic reactivity to motor patterns was best reflected by the Baevsky Stress Index (or Sympathetic Index, SI) that reduced by 45% (P<0.02). We developed a measure of autonomic balance, the SI/RSA ratio that changed from 18.8 to 8.7 (54%; P<0.01) during motor activity and recovered to 16.1 immediately after (P<0.005). The SI/RMSSD reduced by 65% (P<0.01). When HAPWs occurred in quick succession, the parasympathetic activity showed rhythmicity at the HAPW frequency that slowly terminated when motor activity stopped. During motor activity, the heart rate did not significantly change. Conclusions: The major propulsive motor pattern of the human colon, the HAPW as measured by HRCM that is part of the major defecation reflexes, is associated with marked changes in parasympathetic and sympathetic activity that is reflected and measurable as heart rate variability parameters. This opens the way to evaluate autonomic dysfunction in patients with colon motor disorders. Funding Agencies: CIHRNSERC, Farncombe Institute